The Strategy Process / Revised European Edition - Ghoshal Sumantra; Mintzberg Henry; Quin Brian James (Prentice Hall, 1998)
Introduction, Strategy, The Strategy Concept, The Strategist, Strategy Formulation, Strategy Formation, Cases, Organization, Dealing with Structure and Systems, Dealing with Culture and Power, Cases, Context, Managerial Styles, The Entrepreneurial Context, The Mature Context, The Diversified Context, The Professional Context, The Innovation Context, The International Context, The Context of Change, Cases, Bibliography for Readings, Name and Subject Index.
Introduction, Strategy, The Strategy Concept, The Strategist, Strategy Formulation, Strategy Formation, Cases, Organization, Dealing with Structure and Systems, Dealing with Culture and Power, Cases, Context, Managerial Styles, The Entrepreneurial Context, The Mature Context, The Diversified Context, The Professional Context, The Innovation Context, The International Context, The Context of Change, Cases, Bibliography for Readings, Name and Subject Index.